Habeas Viscus : Racializing Assemblages, Biopolitics, and Black Feminist Theories of the Human - Weheliye, Alexander G., 1968- (Book collections on Project MUSE., 2014)
In Habeas Viscus, Alexander G. Weheliye seeks to rectify a major shortcoming of the ""bare life and biopolitics discourse, "" exemplified by the works of Agamben and Foucault, its failure to appreciate the centrality of race to accounts of the human. Working from the vantage point of black studies and drawing especially on the thought of the black feminist theorists Hortense Spillers and Sylvia Wynter, Weheliye suggests alternate ways of conceptualizing the place of race within the dominion of modern politics.